India : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2004 Article IV Consultation highlights that India is on track for another year of robust growth in 2004/05. Supported by a strong monsoon, growth rebounded to 8 1\2 percent in 2003/04, the highest level in more than a decade. In 2005, firms appear to have embarked on a new investment cycle, underpinned by strong credit growth. Inflation has been running higher, driven largely by supply-side factors. The balance of payments position remains comfortable notwithstanding the higher oil prices.